ENERGY DRINKS IN YOUTH: CARDIOVASCULAR, NEUROPSYCHIATRIC, AND POLICY PERSPECTIVES — A NARRATIVE REVIEW - Maja Jabłońska; Agata Bukowska; Ewa Jagodzińska; Zuzanna Jabłońska; Jakub Kaczmarczyk; Joanna Zygadło; Julia Kamińska; Zofia Moskal (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective: Energy drink (ED) consumption has markedly increased among adolescents and young adults, raising clinical and public-health concerns. Evidence links EDs to acute cardiovascular, neuropsychiatric, and metabolic disturbances, yet findings remain fragmented. This narrative review aimed to synthesize recent data on physiological effects, behavioral correlates, and regulatory responses to ED use in youth. Materials and Methods: A narrative search of PubMed (1990–October 2025) identified randomized and crossover trials, observational studies, and PubMed-indexed reviews addressing ED exposure among individuals aged 10–35 years. Six domains were analyzed: cardiovascular, neuropsychiatric, metabolic/gastrointestinal/dental, sport performance, policy and labeling, and medication interactions. Results: Evidence consistently indicates transient increases in systolic and diastolic blood pressure, heart-rate variability changes, and QTc prolongation following ED intake. Cross-sectional and longitudinal studies associate frequent ED consumption with reduced sleep duration, anxiety, depressive symptoms, and higher stress scores. Metabolic data show elevated insulin and glucose levels and rare cases of niacin-related hepatotoxicity. Co-use of EDs with alcohol amplifies risk-taking behaviors and cardiovascular strain. Despite labeling restrictions, marketing continues to target youth, with variable national policy enforcement. Conclusions: ED use among adolescents and young adults exerts measurable short-term cardiovascular and neuropsychiatric effects and contributes to risky behavior patterns. Preventive efforts should combine clinical counseling on caffeine and alcohol co-use with regulatory strategies addressing marketing and accessibility.